On the existence of solutions for two-dimensional Stokes flows past rigid obstacles - Kohr-Ile, M. (Archives of Mechanics, 1996)
In this paper we obtain some existence and uniqueness properties for the solution corresponding to the problem of the plane unbounded Stokes flow past rigid obstacles. The stream function of the flow is represented in the form of simple layer potentials.